Prediction of railway ground vibrations: Accuracy of a coupled lumped mass model for representing the track/soil interaction. Issue 69 (February 2015) - Kouroussis, G.; Verlinden, O.
Abstract: Recent advances in railway-induced ground vibrations showed that the track/soil interaction plays an important role in the low frequency range. This paper contributes to the numerical analysis of train/track/foundation dynamics by presenting the accuracy of a coupled lumped mass (CLM) model devoted to the railway foundations and to the track/soil coupling. Following a summary of the background and the advantages of the CLM model, the coupling strategy is quantified through two application cases. Firstly, the dynamic track deflection is calculated for different railway lines considering various degrees of complexities of foundations. Then, the foundation responses are compared depending on whether detailed coupling is introduced or not. The benefit of the proposed model is emphasized by presenting free-field ground vibration responses generated by a tram and a high-speed train, obtained by a revisited two-step prediction model developed by the authors. Abstract : Highlights: Vehicle/track dynamics strongly depends on the foundation behaviour. A previously developed CLM model is analysed. The foundation responses are compared for quantifying the coupling level. A CLM model is more suitable than a simple Winkler model.